Price and Product Quality Effects on Purchases at UD. Kusuma Bali Mandiri - Adisti Maharani Krisna; Ni Wayan Septia Wini (Pustaka Bangsa Indonesia, 2026)
This study examines the influence of price and product quality on purchasing decisions for furniture products at UD. Kusuma Bali Mandiri, a growing local enterprise in Bali’s competitive furniture industry. It addresses declining purchasing decisions, varying perceptions of price fairness, and inconsistencies in perceived product quality. This quantitative associative study used primary data from structured questionnaires distributed to consumers who purchased furniture within the last year. Data were analyzed using multiple linear regression, supported by validity, reliability, classical assumption, and hypothesis tests through t-test and F-test. The findings reveal that price and product quality positively and significantly affect purchasing decisions, both partially and simultaneously. Product quality has a stronger influence because consumers emphasize durability, design, and finishing. The study implies businesses must maintain competitive pricing and consistent product quality to strengthen purchasing decisions and market competitiveness while supporting long-term customer satisfaction, loyalty, trust, and sustainable business growth in Bali overall.